Pengembangan Model Pelatihan PTK Berbasis Pendampingan untuk Meningkatkan Profesionalitas Guru Matematika SMA di Kabupaten Brebes - Masrukhi Masrukhi; Joko Widodo; Sukestiyarno Sukestiyarno; Tri Joko Raharjo (Universitas Muhammadiyah Surakarta, 2016)
Classroom-based action research (CAR) for high school math teachers is very important to develop their professionalism. To improve the competence of teachers, a development of CAR training model based on mentoring is needed. This study aims to produce an appropriate CAR training model based on mentoring to improve teachers’ professionalism. This study employed research and development (R D) model, then the procedure pursued in this research started from (1) literature study, (2) preliminary field study, (3) needs analysis, (4) preparing the training model design, (5) performing validation model, (6) revising the model, (7) preparing hypothetical model of training, (8) performing limited testing and expanded trials, and (9) revising the final model through the focus group discussion (FGD-2), experts, and practitioners to obtain the final model.The result shows that: (1) the product which is validated by experts and practitioners obtains a mean score of 62.15 (good qualification), (2) the final training model is very feasible to be used by the indication of the its mean score at 3.59 (very high) for its usefulness, the mean score of 3.48 (very high) for its practicality, the mean score of3.58 (very high) for its feasibility. The implementation of training program is alsocapable of producing CAR research reports. The conclusions of research is that the final model of CAR training based on mentoring and its training instruments are very feasible to be used to improve the professionalism of senior high school math teachers in Brebes.